Deoxyribonucleic Acid as a Universal Electrolyte for Bio‐Friendly Light‐Emitting Electrochemical Cells (Adv. Sustainable Syst. 11/2021). (17th November 2021) - Tekoglu, Serpil; Held, Martin; Bender, Markus; Yeo, Guan Ni; Kretzschmar, Andreas; Hamburger, Manuel; Freudenberg, Jan; Beck, Sebastian; Bunz, Uwe H. F.; Hernandez‐Sosa, Gerardo
Abstract : Solid Polymer Electrolytes In article number 2100203, Serpil Tekoglu, Gerardo Hernandez‐Sosa and co‐workers utilize a DNA‐based solid polymer electrolyte (SPE) in the active layer of light‐emitting electrochemical cells (LECs). Thanks to their outstanding electrochemical stability, LEC devices with a variety of emissive materials covering the 400–700 nm spectral range are demonstrated, thus highlighting the universal character of DNA as an SPE system for visible light emission.